Serum vitamin D receptor and fibroblast growth factor-23 levels in postmenopausal primary knee osteoarthritis patients - Yağmur Tekeli Feyza; Özgür Tekeli Seçkin; Köse Özkan (Türk Biyokimya Dergisi, 2022)
The role of vitamin D in primary osteoarthritis (OA) has not been clarified yet. vitamin D receptor (VDR) and fibroblast growth factor-23 (FGF-23) are proteins that play an important role in the metabolism of vitamin D. In this preliminary study, we aimed to examine serum 25-(OH) vitamin D3, VDR, and FGF-23 levels in primary knee OA patients.